2010
DOI: 10.1523/jneurosci.3309-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/Calmodulin Kinase II-Dependent Acetylcholine Receptor Cycling at the Mammalian Neuromuscular JunctionIn Vivo

Abstract: At the mammalian skeletal neuromuscular junction, cycling of nicotinic ACh receptors (nAChRs) is critical for the maintenance of a high postsynaptic receptor density. However, the mechanisms that regulate nAChRs recycling in living animals remain unknown. Using in vivo time-lapse imaging, fluorescence recovery after photobleaching, and biochemical pull down assays, we demonstrated that recycling of internalized nAChRs into fully functional and denervated synapses was promoted by both direct muscle stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 59 publications
3
38
0
Order By: Relevance
“…Comparison of recycled AChR pools in normal vs. chronically denervated muscles showed that in the absence of muscle stimulation most internalized receptors are targeted for degradation, and fewer receptors are able to recycle back into denervated NMJs (Bruneau and Akaaboune, 2006). Conversely, stimulation of denervated muscles increased AChR recycling (Martinez-Pena y Valenzuela et al, 2010), suggesting that stimulation-induced AChR re-stabilization in denervated muscle could be explained by increased AChR recycling. Therefore, we asked whether agrin could also increase AChR recycling at agrin-induced AChR clusters in denervated muscle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of recycled AChR pools in normal vs. chronically denervated muscles showed that in the absence of muscle stimulation most internalized receptors are targeted for degradation, and fewer receptors are able to recycle back into denervated NMJs (Bruneau and Akaaboune, 2006). Conversely, stimulation of denervated muscles increased AChR recycling (Martinez-Pena y Valenzuela et al, 2010), suggesting that stimulation-induced AChR re-stabilization in denervated muscle could be explained by increased AChR recycling. Therefore, we asked whether agrin could also increase AChR recycling at agrin-induced AChR clusters in denervated muscle.…”
Section: Resultsmentioning
confidence: 99%
“…However, as shown previously for synaptic AChRs, full stabilization of AChRs in ectopic, agrin-induced AChR clusters to a half-life of 10–14 days also requires muscle activity. Of note, muscle stimulation can promote the translocation of internalized receptors from the internal pool into the postsynaptic membrane in denervated synapses (Martinez-Pena y Valenzuela et al, 2010). Thus, the increase in AChR stability by muscle activity could be explained at least in part by an increase in the delivery of recycled AChR into induced clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Our results for endocytotic and recycling markers indicate that an up-regulation of this pathway did occur, which was confirmed in a functional assay of nAChR recycling, suggesting that an increase in endocytosis/ receptor recycling may account, in part, for the observed receptor up-regulation upon prolonged exposure to A␤. How this up-regulation in recycling is induced will be the subject of future studies, focusing, in particular, on calcium-regulated pathways (52) and A␤ internalization (53). Nonetheless, it is proposed that up-regulation of the nAChRs with sustained, elevated levels of A␤ leads to a feed-forward dysregulation of calcium homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…4). Although we cannot exclude the possibility that rab11 exerts its function directly on AChR trafficking, recycling of AChR receptors has been observed only at mature NMJs and only in response to muscle stimulation (Bruneau and Akaaboune, 2006;Martinez-Pena y Valenzuela et al, 2010), whereas at the stage of AChR pre-patterning when we examined rab11-dependent trafficking, NMJs have not yet formed. Combined with the observations that MuSK is crucial for localization of Dishevelled to presumptive endosomes, and that Dishevelled function in muscle cells is crucial for AChR pre-patterning and axon guidance (see below) (Jing et al, 2009), we favor the idea that rab11 regulates primarily MuSK localization and function.…”
Section: Musk Receptor Localization To Recycling Endosomes Is Crucialmentioning
confidence: 91%